The effect of ionizing radiation on chloramphenicol - Marciniec, Barbara; Stawny, Maciej; Kozak, Maciej; Naskrent, Marek (Springer Netherlands, 2006)
The effect of ionizing radiation on the physicochemical properties of chloramphenicol in solid state has been studied. The compound was e-beam irradiated with doses from the range 25–400 kGy and the possible changes were detected in the organoleptic methods (colour, form, odour, solubility and clarity), by SEM observations, X-ray, chromatography (TLC), spectrophotometry (UV, IR, EPR) and thermal (DSC) methods. No significant changes relative to the unirradiated sample were observed as a result of irradiation with the dose of 25 kGy – a standard dose for radiation sterilization, besides free radicals generation. Higher doses were found to produce a change in colour, increase in absorbance (UV), changes in the XRD spectra and appearance of products of radiolysis. The presence of the radiolysis products was confirmed by the TLC method, indirectly by DSC showing a decrease in the melting point from 0.2 to 4.5°C and enthalpy from 3.8 to 23.3 J g–1, respectively. A linear relationship was obtained between the irradiation dose (25–400 kGy) and the melting point of chloramphenicol, characterised by the correlation coefficient r=0.9968. The EPR signal intensity increased with increasing dose of irradiation and the lifetime of the free radicals was longer than 6 months. No changes were detected in SEM and IR spectra. As follows from our results, the DSC method is most suitable for a fast monitoring of the drugs subjected to sterilization by irradiation as it permits detection of changes occurring even on irradiation with low doses and their quantitative description.
Keywords: drug analysis; DSC; EPR; IR; radiation sterilization; radiolysis in the solid state; SEM; TLC; UV; X-Ray